Interaction of 4 allotropic modifications of carbon nanoparticles with living tissues - S. Ya. Paryzhak; T. I. Dumych; S. M. Peshkova; E. E. Bila; A. D. Lutsyk; A. Barras; R. Boukherroub; S. Szunerits; R. O. Bilyy (The Ukrainian Biochemical Journal, 2019)
Environmental pollution and technological progress lead to carbon nanoparticles that pose a serious health risk. They are present in soot, dust, and printing toner and can also be formed during grinding and cutting. Human neutrophils are able to sequester foreign material by formation of neutrophil extracellular traps (NETs), a process that can cause a strong inflammatory response. In the current work we compared proinflammatory properties of different carbon-based nanostructures: nanodiamonds, graphene oxide, fullerenes C60 and carbon dots. We tested adjuvant properties of carbon nanoparticles in a murine immunization model by investigating humoral (specific IgG and IgM antibodies) and cellular (delayed type hypersensitivity) immune responses. The ability of NETs to sequester nanoparticles was analyzed in a mouse air pouch model and neutrophil activation was verified by in vivo tracking of near-infrared labeled nanodiamonds and ex vivo fluorescent assays using human blood-derived neutrophils. All carbon nanoparticles exhibited proinflammatory adjuvant-like properties by stimulating production of specific IgG but not IgM antibodies (humoral immune response). The adjuvant-like response decreased in this order: from nanodiamonds, graphene oxide, fullerenes C60 to carbon dots. None of the studied carbon nanoparticles triggered a delayed type hypersensitivity reaction (cellular immune response). Nanodiamonds and fullerenes C60 were sequestrated in the body by NETs, as confirmed in the air pouch model and by in vivo fluorescent tracking of near-infrared labeled nanodiamonds.